Persona-based expert review of an e-learning system for adults - Stojmenova, E.; Lugmayr, Artur; Dinevski, D. (2013)
In the last decade, e-learning has witnessed an unprecedented expansion at all levels and modes of education at a global level. Once the barriers of the internet access are overcome and the basic digital literacy of learners is achieved, e-learning has the obvious potential to make adult learning more effective, efficient and pervasive. In order to entirely exploit the potential of e-learning systems, besides content and technical feasibility, some additional aspects, such as acceptance and usability issues, have to be taken into account. One of the possible ways to provide for good usability and acceptance of an e-learning system is to involve the target users of the e-learning services throughout the entire design and development processes. However, this can be both time- and cost-consuming. Therefore, in this paper, we present how persona- and scenario-based usability expert reviews can be used to test and improve the usability of an e-learning system on the case example of the E-CHO e-learning system. © 2013 IEEE.